Investigating Local Climate Zones for Outdoor Thermal Comfort Assessment in an Indian City - Kotharkar, Rajashree; Bagade, Anurag; Agrawal, Abhay (Geographica Pannonica, 2019)
The rapid growth of development and urbanization in the Indian subcontinents has made the urban areas vulnerable to outdoor thermal discomfort (OTC) which is in turn affecting the quality of living in these areas. This study aims at evaluating spatiotemporal dynamics of outdoor thermal comfort in Nagpur city (India) during winter, summer and heat wave period using Local Climate Zone (LCZ) classification. It uses Thom’s Discomfort Index (DI) and Relative Strain Index (RSI) to analyze outdoor thermal comfort. It also examines the significance of major LCZs in addressing thermal anomaly and OTC at different time periods using One-way ANOVA technique. It identifies critical LCZ having a maximum exposure of discomfort and concludes with the applicability of LCZ for addressing discomfort.